2021
DOI: 10.1111/eip.13227
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 pandemic's effects and telehealth in Early Psychosis Services of Quebec, Canada: Will changes last?

Abstract: Aim To explore the impacts of the COVID‐19 pandemic first wave in Quebec, Canada on practices in early intervention services (EIS) for first‐episode psychosis, including reorganization of clinical and administrative practices and teleconsultation use. Methods Adopting a cross‐sectional descriptive study design, a 41 questions online survey was sent to the team leaders of all the 33 Quebec EIS, of which 100% responded. Data were collected from 18 May to 4 June 2020 and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…The survey showed that the majority of practitioners were supportive in continuing to use telepsychiatry and would recommend REACTS. Also, the results from our study and previous research that report technical issues and limited technical support as barriers to using telepsychiatry (Pires de Oliveira Padilha et al, 2021; Guinart et al, 2021; Lal et al, 2022) highlight the importance of making support available to those who need it when they need it.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The survey showed that the majority of practitioners were supportive in continuing to use telepsychiatry and would recommend REACTS. Also, the results from our study and previous research that report technical issues and limited technical support as barriers to using telepsychiatry (Pires de Oliveira Padilha et al, 2021; Guinart et al, 2021; Lal et al, 2022) highlight the importance of making support available to those who need it when they need it.…”
Section: Discussionsupporting
confidence: 72%
“…Although the implementation was not initially successful, the deployment of a new version of REACTS and the provision of booster trainings facilitated a rapid increase of its use at the onset of the pandemic (Lal et al, 2022). This is of particular relevance given that other settings had not established such a foundation and as such providers were left to rely on platforms inappropriate for patient care such as Zoom's free version, Skype, Facetime, Messenger, and WhatsApp (Pires de Oliveira Padilha et al, 2021), or mainly restrict care to a phone‐based approach until alternatives were established. The survey showed that the majority of practitioners were supportive in continuing to use telepsychiatry and would recommend REACTS.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a survey on early intervention services for first-episode psychosis during the first wave of the COVID-19 pandemic in Quebec found limitations regarding clinicians’ levels of ease with teletherapy, as well as lack of technical support and availability of telehealth equipment ( 49 ).…”
Section: Resultsmentioning
confidence: 99%
“…Many articles that supposedly focused on MDs did not discuss the specific impact on each MD as experienced by patients; rather, they focus on the delivery of services, acceptability, training, and guidelines. In fact, little is known about the impact of the online setting on the treatment of first-episode psychosis ( 49 ), eating disorders ( 54 ) or developmental disorders ( 50 ). An exception was found in a work on trauma therapy, which reported a barrier to teletherapy for PTSD patients with cognitive impairment ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…This would allow reaching YEP who live in sparsely populated remote regions where distances to be travelled to get to the EIS are significantly longer and represent a major barrier to in-person PA interventions. Indeed, collaboration between EIS could address barriers such as small patient pools and limited clinical human resources to offer group intervention, especially in small remote centers 43 . Moreover, a majority of Quebec EIS reported being interested in participating in a multiregional teletherapy 16 16 group and in a training program on the use of technologies for telehealth 43 , which could help its implementation to ensure continuity of care even during situations such as COVID-19 related restrictions 44,45 .…”
Section: Peer Supportmentioning
confidence: 99%